Robert Spaemann's philosophy of the human person: nature, freedom, and the critique of modernity - Zaborowski, Holger (Oxford theological monographs, 2010)
An analysis of the most important features of Robert Spaemann's philosophy. Holger Zaborowski demonstrates the importance of Spaemann's contribution to a number of contemporary debates in philosophy and theology and explains the unity of his thought